Radiation Detection and Measurement textbook - Knoll G. F. Glen (Student Solutions Manual)
As a way to learn Mathematica while teaching the associated laboratory course, this author gradually compiled a complete set of solutions to the Radiation Detection and Measurement problems. Unfortunately, while many students appreciated having the solutions, and in particular the detailed manner in which they are derived, they did not appreciate the elegant but unfamiliar Mathematica language needed to produce them. Of course, the intent was to teach them an elegant software tool for doing mathematics while providing them with solutions that they could interact with.